ASSESSING RISK AND HAZARD IN FLIGHT OPERATION OF FLYING SCHOOL: CASE STUDY USING HAZARD IDENTIFICATION AND RISK ASSESSMENT METHOD - Noorwahyu, Arsanto; Widodo, Dody Wahyu; Widadgo, Rinosa Ari; Aviantara, Gema (GoAcademica Research dan Publishing, 2025)
Safety is at utmost priority in aviation industry. The International Civil Aviation Organization even established a dedicated part of its regulation, The Annexes, to ensure and promote aviation safety. The state of establishing, assessing risk, assuring, and promoting safety is a holistic system stated as Safety Management System. This system ensures that risks and hazard are mitigated and reduced to an acceptable level. There are many procedures and checklists available to ensure flight safety, one of them is by assuring the conduct of safety procedure is based on its establishment standard or even revised and updated to follow the recent development in the operation of the industry. This research is qualitative-research using the Hazard Identification and Risk Assessment method. The output of this research will be a mitigation recommendation that corresponds with the result of hazard identification and assessment of the researched phenomenon so that the same incident would not happen again in the future. This research is conducted in the oldest aviation campus in Indonesia, Politeknik Penerbangan Indonesia Curug. The final result is that the operation of flight training still tends to have either hazard or risk. This research aims to encourage and promote mitigation act to reduce and prevent the aftereffect of the risk assessed.